2020
DOI: 10.1111/1365-2656.13310
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between seed‐dispersing ant species affect plant community composition in field mesocosms

Abstract: 1. In generalized mutualisms, species vary in the quality of services they provide to their partners directly via traits that affect partner fitness and indirectly via traits that influence interactions among mutualist species that play similar functional roles. Myrmecochory, or seed dispersal by ants, is a generalized mutualism with ant species varying in the quality of dispersal services they provide to their plant partners. Variation in ant species identity can directly impact seed dispersal patterns and pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 102 publications
(180 reference statements)
0
9
0
Order By: Relevance
“…Ant nests emit high amounts of CO 2 and are therefore spots of high metabolic activity (Risch et al, 2005). In many plant communities, ants are important seed dispersers affecting the distribution of plant species (Prior et al, 2020), and many ant species form mutualistic relationships with plants and myrmecophilous insects, altering the distribution of the species connected within these ecological networks (Ness et al, 2010). With their stationary and perennial colonies, which restrict the activity and foraging of workers to an area close to the nest (Blüthgen & Feldhaar, 2010), ants have relatively constant populations at a site and can thus be reliably monitored and easily sampled in a standardized way, which makes them established indicator organisms (Alonso, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Ant nests emit high amounts of CO 2 and are therefore spots of high metabolic activity (Risch et al, 2005). In many plant communities, ants are important seed dispersers affecting the distribution of plant species (Prior et al, 2020), and many ant species form mutualistic relationships with plants and myrmecophilous insects, altering the distribution of the species connected within these ecological networks (Ness et al, 2010). With their stationary and perennial colonies, which restrict the activity and foraging of workers to an area close to the nest (Blüthgen & Feldhaar, 2010), ants have relatively constant populations at a site and can thus be reliably monitored and easily sampled in a standardized way, which makes them established indicator organisms (Alonso, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that overall, other ant species do not have a direct antagonistic interaction with seeds or mutualist partners. This is an interesting finding, as it is generally predicted that other ants negatively affect dispersal directly (by being antagonistic or low quality partners) or indirectly by outcompeting the good disperser (Ness 2004;Giladi 2006;Ness et al 2009;Prior et al 2020;Parker et al 2021). Habitat factors in both the combined and remnant path analysis influenced other ant species abundance, which suggests that the other ant species were more abundant in microhabitats that also favored Aphaenogaster sp.. During the seed removal trials, we only observed two other ant species interacting with, but not removing, seeds: the native species Lasius americanus and the invasive species Nylanderia flavipes, with the latter occurring at high abundances and removing parts of elaiosomes.…”
Section: Discussionmentioning
confidence: 78%
“…Another source of variation we did not account for, is that we pooled Aphaenogaster species given that they are challenging to tell apart in the field. Emerging work, including our own, suggests that mutualistic partner identity (among Aphaenogaster putative species and populations) can affect seed dispersal function Prior et al 2015;Meadley Dunphy et al 2020;Prior et al 2020;Buono et al 2022). Also, we controlled for 11 rodent impacts on seed dispersal, but variation in this antagonistic interaction could also be contributing to how HLUC affects this mutualism (Ness & Morin 2008).…”
Section: Discussionmentioning
confidence: 92%
“…Several exotic animal species can outcompete native dispersers or affect their dispersal behavior [ 12 , 13 ]. They may also facilitate the introduction of exotic plants by dispersing them and enhancing seedling recruitment success [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%